If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 3 = 1x + 4 Reorder the terms: 3 + 9x = 1x + 4 Reorder the terms: 3 + 9x = 4 + 1x Solving 3 + 9x = 4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 9x + -1x = 4 + 1x + -1x Combine like terms: 9x + -1x = 8x 3 + 8x = 4 + 1x + -1x Combine like terms: 1x + -1x = 0 3 + 8x = 4 + 0 3 + 8x = 4 Add '-3' to each side of the equation. 3 + -3 + 8x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = 4 + -3 8x = 4 + -3 Combine like terms: 4 + -3 = 1 8x = 1 Divide each side by '8'. x = 0.125 Simplifying x = 0.125
| 170=65+(20+8)x | | 4u+49=-5(u+1) | | 3r-5=7r+7 | | -119=7+7m | | 4x^2y^3= | | 18v-24=0 | | -10=-9+12x | | x-2+2=-2 | | logx(12)=1 | | -3+27= | | 20x+8x-6x+20= | | 13=4x+5 | | 12+x=5-6x | | -x^3+x^2=0 | | 60x+10y=41 | | 44=1/2x8 | | 7x+29=25 | | 44=1/2•8 | | R^2-14r-18=9 | | x^2-4-x^3+4x=0 | | 2x+62=5x | | X-12+x+21=-1 | | 3(-5)-4=-55 | | -5-8x=-61 | | 5ax+3x=bx+5 | | 6y+33=9y | | 4/ln2 | | 4/ln(^2)2 | | -2x+3=4x+2 | | -4(4x-5)-2x-4=-5 | | 5x/12−y=9 | | 3(8x-1)=16x+53 |